Strategi Inovatif Pembelajaran Eksplorasi Strategi Inovatif Pembelajaran Biologi di Abad 21: Strategi Inovatif Pembelajaran Biologi di Abad 21 - Arine Ellen Rose; Ayu Nency; Egi Sudira; Yesaya Haria; Ade Suryanda (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Biology education in the 21st century faces challenges and opportunities that have never been imagined before along with advances in technology and changes in learning dynamics. The digital era demands the exploration of innovative strategies so that students not only understand biological concepts theoretically, but are also able to apply them in real-world contexts. This article explores several innovative strategies, such as Project Based Learning, Problem Based Learning, Cooperative Learning, Discovery Learning, and Inquiry Learning, which are considered the cornerstones of biology education in the 21st century. The importance of developing student skills, including critical thinking, creativity, and collaboration, is a major focus in innovative biology education. Globalization, digital technology and international cooperation influence learning dynamics, providing unlimited access to biological knowledge from around the world. The research method uses a literature study approach and qualitative methods to explore innovative strategies in biology learning in the 21st century. The results of this research provide in-depth insight into various learning models, such as Project Based Learning, Problem Based Learning, Cooperative Learning, Discovery Learning, and Inquiry Learning, as well as identifying challenges and opportunities in implementing this innovative strategy. This means that innovative biology education in the 21st century requires a holistic approach that integrates knowledge, skills and real-world context to prepare students to face the complexity of global challenges.